AGN rate in cosmic filaments - Perez, Noelia Rocío (2019)
Filaments, clusters, sheets and voids are the building blocks of the cosmic web and galaxies in filaments representing approximately half of the baryon mass in the universe. Different properties of galaxies are correlated with their location within the filamentary structures. In particular, the presence of AGN galaxies requires particular environmental conditions. The results on the dependence of the AGN rate with respect to the proximity and filament properties are shown in this work.